Revenge and/or justice : the portrayal of Electra in drama with special reference to the modern plays of Hofmannsthal, O'Neill, Giraudoux, and Yourcenar - De Marre, Martine (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1988.